Effects of Pretreatment on the Electronic Properties of Plasma Enhanced Chemical Vapor Deposition Hetero-Epitaxial Graphene Devices - 张连昌 史志文 杨蓉 黄鉴 (Chinese physics letters, 2014)
Quasi-monolayer graphene is successfully grown by the plasma enhanced chemical vapor deposition hetero- epitaxial method we reported previously. To measure its electrical properties, the prepared graphene is fabricated into Hall ball shaped devices by the routine micro-fabrication method. However, impurity molecules adsorbed onto the graphene surface will impose considerable doping effects on the one-atom-thick film materiM. Our ex- periment demonstrates that pretreatment of the device by heat radiation baking and electricM annealing can dramatically influence the doping state of the graphene and consequently modify the electricM properties. While graphene in the as-fabricated device is highly p-doped, as confirmed by the position of the Dirae point at far more than ＋60 V, baking treatment at temperatures around 180~C can significantly lower the doping level and reduce the conductivity. The following electricM annealing is much more efficient to desorb the extrinsic molecules, as confirmed by the in situ measurement, and as a result, further modify the doping state and electrical properties of the graphene, causing a considerable drop of the conductivity and a shifting of Dirac point from beyond 4-60 V to 0V.